A Partially Purified Acinetobacter baumannii Phage Preparation Exhibits no Cytotoxicity in 3T3 Mouse Fibroblast Cells - Henein, Alexandra E.; Hanlon, Geoffrey W.; Cooper, Callum J.; Denyer, Stephen P.; Maillard, Jean-Yves (Frontiers in Microbiology, 2016)
A surge in the level and scale of antibiotic resistance has prompted renewed interest in the application of bacteriophages to treat bacterial infections. However, concerns still exist over their efficacy and safety. The cytotoxic effect of a single Acinetobacter baumannii phage was evaluated in mouse fibroblast 3T3 cells using four different assays: trypan blue; staining with Hoechst and propidium iodide; lactate dehydrogenase release; and the MTS assay. The addition of phage concentrations up to 2 x 109 pfu/mL showed little to no impact on the viability of 3T3 cells after 24h exposure using the different assays. This study demonstrates that phage BS46 is non-cytotoxic to 3T3 cells using four different assays and that appropriate quality assurance protocols for phage therapeutics are required.